The Effect Of Debt To Equity Ratio, Current Ratio, Return On Asset, Total Aset Turn Over Towards Income Growth - Sinurat, Manogar; Priya, RK. Sri; Sitanggang, Romian; Sitorus, Friska Darnawaty (Gorontalo Accounting Journal, 2021)
The purpose of this study is to analyze the effects of Debt To Equity Ratio, Current Ratio, Return On Aset, Total Asset Turn Over on profit growth. The samples used are on IDX, a manufacturing company in the consumer goods industry sector in the 2016-2019 period. The method used is a quantitative approach. Purposive sampling was used in the sample selection method. Multiple linear regression analysis, hypothesis determination coefficient test, simultaneous hypothesis test (f-test), and also partial (t-test) were used as data analysis techniques. The results of the research partially detected that DER and CR haven't given effect and haven't signed, ROA and TATO partially affect positively and significantly the profit growth of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period, while simultaneously DER, CR, ROA, and TATO significantly influence earnings growth.